THE RELATIONSHIP BETWEEN MOTHER'S KNOWLEDGE AND ATTITUDE WITH EXCLUSIVE BREASTFEEDING IN GAMPONG CEURIH, ULEE KARENG SUB-DISTRICT, BANDA ACEH - Nevariza (Aceh Sanitation Journal, 2022)
Exclusive breastfeeding is breastfeeding from birth until the baby is 6 months old. The achievement of exclusive breastfeeding in Aceh in 2019 is 55%. The main cause is the low knowledge of mothers in exclusive breastfeeding. Early and exclusive breastfeeding will help prevent various childhood diseases, especially gastric disorders, respiratory tract and asthma in children. This study was to determine the relationship between the knowledge and attitudes of mothers with exclusive breastfeeding. This type of research is analytic cross-sectional. Samples were taken using a total sampling technique of 47 mothers who had babies aged 6-12 months in Gampong Ceurih, Ulee Kareng District, Banda Aceh. The analysis was carried out using the chi-square test to determine the relationship between variables. The results of this study indicate that there are 46.8% of a baby did not get exclusive breastfeeding and 53.2% of babies got exclusive breastfeeding. There is a relationship between the mother's knowledge (p = 0.015) and the mother's attitude (p = 0.023) with exclusive breastfeeding. This study concludes that there is a relationship between the knowledge and attitudes of mothers with exclusive breastfeeding. Researchers suggest that it is necessary to provide health education about exclusive breastfeeding to the whole community, especially mothers who have babies about the benefits of exclusive breastfeeding so that people or mothers who have not given exclusive breastfeeding to their babies can increase their knowledge and will provide exclusive breastfeeding to their babies